Forensic Analysis of Web Browser Artifacts using Open-SourceTools - Rajeev Kumar; Amit Yadav; Aman Kumar; Ketan Baranwal (Indian Journal of Forensic Medicine and Pathology, 2025)
Nowadays, number of computer-related crimes is concerningly in growth these days, therefore digital forensic investigation is essential to combating crimes like cyberbullying, fraud, and cyber intrusion with its advanced capabilities, digital forensics is a fascinating 𿿿eld that can minimize and examine such angers. Digital forensic investigation’s primary objective is to ensure that any evidence is not tampered with and is kept in its purest form possible. The most common tool for get into online information is a web browser, which also assists as a user’s interface with the outside world. Web browsers are used by internet users for a variety of online tasks, including email, social networking, banking, 𿿿le ad deo downloads, and internet sur𿿿ng. Since a web browser is the only mans accessing the internet, cybercriminals either utilize or target web browsers to perform internet-related crimes. There are many other browsers on the market, including Opera, Safari, Google Chrome, Mozilla Firefox and Internet Explorer to name a few. However, Google Chrome is the most widely used browser among internet users. Gathering and examining web browser-related artifacts from the suspect’s device is crucial for digital forensic investigator and especially for computer forensic detectives. To help the investigator with their work, these artifacts may be recovered using a speci𿿿c browser forensic tool.